Prevalence of Premenstrual Syndrome (PMS) Among Female Biomedical Students in Kabul, Afghanistan: A Cross-Sectional Study - Tawakoli MF; Abed A; Sakhi R (International Journal of Women's Health, 2025)
Mohammad Farid Tawakoli, Abdullah Abed, Rohullah Sakhi Public Health Faculty, Kabul University of Medical Sciences, Kabul, AfghanistanCorrespondence: Mohammad Farid Tawakoli, Public Health Faculty, Kabul University of Medical Sciences, Kabul, Afghanistan, Tel +93 77 0017564, Email Faridtavakoli313@gmail.comBackground: Premenstrual Syndrome (PMS) is a significant public health concern affecting a substantial proportion of women worldwide, with a global prevalence of approximately 47.8%. In Afghanistan, the PMS is prevalent, and the magnitude is unknown. Due to a lack of studies, this is the first study that sheds light on prevalence of PMS.Objective: This study investigates the prevalence and symptoms of PMS among female students in Kabul, Afghanistan.Materials and Methods: This descriptive cross-sectional study was conducted between May and September 2024 on a sample of 285 students. A systematic and stratified random sampling method was employed. Data were collected using a standardized questionnaire and analyzed using SPSS version 26. The chi-square test was performed to assess the association between PMS prevalence and variables such as age and menstrual cycle status.Results: The study achieved a response rate of 84.91%. The participants’ age distribution was 39.7% between 18– 20 years, 57% between 21– 25 years, and 3.3% above 25 years. Most participants were single (87.6%), and 76.9% reported having regular menstrual cycles. The prevalence of PMS was 72.3% based on ICD-10 criteria and 21.1% based on ACOG criteria. The chi-square test indicated no statistically significant association between age groups and PMS prevalence (p-value= 0.151), but significant relationship was observed between menstrual cycle regularity and PMS prevalence (p-value= 0.018). The most frequently reported symptoms were muscle, joint, and back pain (86.8%), fatigue (84.3%), and reduced interest in activities (77.3%).Conclusion: The high prevalence of PMS and its association with irregular menstrual cycles highlight the need for targeted awareness campaigns, culturally sensitive interventions, and improved healthcare access to mitigate its effects.Keywords: menstruation, premenstrual syndrome, premenstrual disorder, prevalence